EFEITOS DA COVID-LONGA NO PERFIL INFLAMATÓRIO DE PACIENTES E ESTUDO DE UMA NANOEMULSAO A BASE DE ACAÍ PARA MODULAÇÃO DA INFLAMACÃO PULMONAR - Souza, Diulie Valente de (2024)
COVID-19, a disease caused by the SARS-CoV-2 virus, began in December 2019 in Wuhan, China, and continues to this day. However, with the increase in vaccination, there has been a significant impact on reducing the severity of COVID-19. Although there is vaccination against SARS-CoV-2, viral infection and transmission are still possible and to date there are no therapeutic alternatives with curative capacity. Açaí (Euterpe olarecea Mart.) has already recognized anti-inflammatory activity. However, there are still no studies demonstrating its effect in models of pulmonary inflammation, either in its free form or in nanostructured form. Therefore, this study aimed to analyze the socioepidemiological profile and the effects of long COVID in individuals recovered from SARS-CoV-2 infection, focusing on the role of the NLRP3 inflammasome in pulmonary inflammation. In addition, it explored the anti inflammatory potential of free and nanostructured açaí extract to attenuate the inflammatory response associated with the disease. The methods included analyzing the socioepidemiological profile of the volunteers as well as comorbidities, symptoms, and sequelae. In addition, the expression of IL-6, TNF-α, IFN-γ, and NLRP3 genes in blood samples from these individuals was performed to understand the relationship with inflammation and sequelae of COVID-19. In vitro analyses were also performed to evaluate the effect of açaí extract and a nanoemulsion containing such extract on the activation of the NLRP3 inflammasome and on inflammation induced by different experimental models including LPS, nigericin, and SARS-CoV-2 Spike protein. A computational analysis was also performed to investigate the possible interaction of the açaí chemical matrix with NLRP3. The study included 74 volunteers, mainly women and aged between 31 and 50 years old. Most had a high school education and a family income of 1 to 3 minimum wages. The most common symptoms during the infection were headache, loss of taste and smell, and body pain. After recovery, 69% of the individuals reported sequelae such as memory loss, hair loss, fatigue, and anxiety. Gene expression analysis revealed that IL-6 was significantly increased in patients with cognitive and respiratory sequelae, and these conditions are closely related to the presence of previous metabolic diseases. The açaí powder extract presented 13 different bioactive molecules, the most abundant being epicatechin, luteolin, apigenin, and cynanidin-3-O-rutinoside. The nanoemulsion containing 0.83 mg/mL of extract was developed by the spontaneous emulsification method, which presented an average size of 160 nm (±0.9), PDI of 0.146 (±0.01), zeta potential of -12.5 (±0.7) and pH of 8.6 (±0.08). Four experimental models mimicking the different mechanisms of NLRP3 inflammasome activation were used to evaluate the anti-inflammatory capacity of free and nanostructured açaí extract in lung cells (A549). This research demonstrated that COVID-19 can cause significant sequelae, especially in individuals with comorbidities. It was also possible to observe that both the free extract and the nanoemulsion demonstrated potential to reverse cellular damage induced by inflammation, with the nanoemulsion showing greater efficacy in reducing nitric oxide levels, potentially reducing lung inflammation. Therefore, the nanoemulsion used in this study may be an anti-inflammatory therapeutic alternative to help with inflammation in COVID-19. The results suggest that açaí may be a promising alternative in the treatment of inflammation associated with long COVID, highlighting the importance of considering socioeconomic factors in the impact of the pandemic.